How universities participate in agricultural extension: a comparative study of two Chinese agricultural universities - Shan, Yan, author; Taylor, Peter Leigh, advisor; Swanson, Louis, committee member; Carolan, Michael, committee member; Cabot, Perry, committee member; Opsal, Tara, committee member (Colorado State University. Libraries, 2022)
University-based agriculture extension is a system set up to help local farmers access the newest agricultural technology and techniques developed by universities, which is comparatively different from the traditional government-led approach. US is currently the only country in the world which has based this service within the university, yet many other developing countries have started to incorporate universities into their agricultural extension system in order to improve the effectiveness of the agricultural extension services. However, little literature pays attention to how the universities adopt this practice and how this adoption influences the organizational capacity of universities. This study tries to fill this gap by exploring how two Chinese agricultural universities adopted two different ways to build platforms for conducting agricultural extension, how these newly built platforms impact agricultural extension activities, and what the future for these new platforms looks like in terms of institutionalization. This dissertation draws on relevant literature of organization theory and rural sociology to frame the innovation process happening in these two agricultural universities. The research questions which this dissertation tries to answer are: 1) How did the university incorporate this new function into their daily practices; 2) What kind of organizational changes did they experience? Is there a better way to do this? 3) How might this new practice in the university influence the previously existing agricultural extension system? To explore these questions, I conducted a comparative case study that included: 1) semi-structured in-depth interviews with key informants; 2) direct field notes from the local sites of universities; 3) secondary documents including collaboration contracts, university handouts, news reports, official websites etc. There are several major findings from this dissertation research. First, the two universities both made within-organizational change and outside-organizational change. They had similar within-organizational change which is clearly required by the national policy to build a new institute for extension within the university. But the New Institute faced different issues of legitimacy in the two universities. With regard to outside organizational change, the two universities built different kinds of platform to conduct agricultural extension activities, one established physical land with all kinds of facilities and the other one is project oriented. Different platforms bring the two universities both unique advantages and distinct challenges. Second, with these organizational changes, the new practice of agriculture extension transformed their previous singular, sporadic individual activities of agriculture extension by upscaling the extension team and funding for the activities. Third, though via different platforms, the two universities face similar challenges of institutionalizing university-based extension. With the platform with physical land comes with the issue of development differentiation and the platform based on projects lacking a stable safeguard mechanism. Fourth, the decision of how to build platforms is not a standalone issue but is related to the history, current economic and political conditions of each of the universities. This dissertation contributes to theory by illuminating the process of how university organizations change or innovate to fulfill the new role of university-based agricultural extension. Based on the findings from this study, I argue that universities need support from local governments or local agribusiness to fulfill this new role of agricultural extension, otherwise the advantages of university in agriculture extension cannot be realized. There is no certain path universities need to follow to complete this task and it depends on the local situation and the social contexts of each university. Lastly, this dissertation contributes to methodology with its comparative in-depth case study of institutional innovation in Chinese universities. What's more, this study also proposes some practical suggestions for universities to consider when creating their own agricultural extension platforms and partnerships with local governments and local agribusiness to promote agricultural extension. This study also shows the need for further study related to the future development of these newly built university-based agricultural extension and the organizational capacity of universities to become involved in agricultural extension across different locations and social contexts.